Some experiments on the effect of oil pollution on the marine alga Enteromorpha flexuosa (wulf.ex.roth) - Mohd. Nasir Saadon (Fakulti Pengajian Maritim dan Sains Marin, 2011)
The culturing of Enteromorpha flexuosa was carried out under laboratory conditions in Erd-Schreiber culture medium. Two volumes of Tapis A crude oil (0.1 ml/litre and 1.0 ml/litre) were used in the preparation of Erd-Schreiber culture media containing oil to which the E. flexuosa germlings were introduced as a temporary treatment.